Fiscal Consolidation : what Differences between Shock Therapy and Soft Adjustment? - Durand, Jean-Jacques; 'Oeillet, Guillaume L (DEMO, 2020)
After easing fiscal policies during the economic crisis, many countries faced a rising public debt and most of them have launched fiscal consolidation plans to stabilize and reduce the public indebtedness in order to restore the sustainability of the public finances. Two different strategies can be followed by policymakers to achieve this goal. The first approach is a shock therapy that would response to a financial emergency keeping away a potential default. A second approach smoothes the fiscal adjustment to limit contractionary effects. In this paper, we compare the macroeconomic effects of each strategy based on the narrative approach of the fiscal consolidations developed by the IMF rather than the conventional statistical measure (cyclically-adjusted primary balance: CAPB) measure. Both strategies show similar effects on the macroeconomic variables, but private demand would react stronger to the shock therapy strategy.(original abstract)